Maturity models of education information systems and technologies: a systematic literature review - Vidal de Carvalho, Joao (2018)
Maturity models (MM) have been introduced, over the last five decades, as guides and references for the information system management in organizations from different sectors of activities. In the education sector, MM have also been used to evaluate higher education institutions (HEI) in several dimensions, such as ICT, management, process management, course curricula, course/HEI accreditation, e/m-learning, online courses and pedagogical strategies. The HEI have an enormous complexity due to the specificity and quantity of their processes, demanding capable information systems (IS) and tools to manage these IS. Based on the guidelines of a methodology for a systematic literature review, the MM of different subareas of education are identified and categorized in this paper. For each MM associated with HEI IS, it is identified the methodology of development and validation, as well as the scope, stages and their characteristics by dimensions. This study resulted in the need to develop a MM for IS that supports HEI in their core business activities and management.